1975
DOI: 10.1577/1548-8659(1975)104<277:pcsolb>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Community Structure of Largemouth Bass, Warmouth, and Bluegill in Lake Fort Smith, Arkansas

Abstract: Fish parasite community structure was studied on largemouth bass, warmouth, and bluegill from Lake Fort Smith, Arkansas during July 1970 through June 1971. Individual diversity () did not fluctuate appreciably on a seasonal basis in any of the hosts. When individual diversity () increased, redundancy (R) tended to decrease, and vice versa. Community diversity () displayed greater seasonal fluctuations than individual diversity (), with highest values in late winter and early spring. There was no significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The first definition of a parasitic community was given by Cloutman (1975) who said that it is "the complex of individuals belonging to the different parasite species inhabiting a host". Studies focusing on the structure of parasite communities in marine fish, in terms of diversity, are scarce.…”
mentioning
confidence: 99%
“…The first definition of a parasitic community was given by Cloutman (1975) who said that it is "the complex of individuals belonging to the different parasite species inhabiting a host". Studies focusing on the structure of parasite communities in marine fish, in terms of diversity, are scarce.…”
mentioning
confidence: 99%
“…Liver fibrosis and intensities of larval parafishes generally contain greater parasite burdens, reduced sites in bluegills levels of prevalence and intensity would be expected in remaining pond 2 fish. Intensity (n) The correlation between age (age-class) and infection inLiver Pericardium tensity in bluegills ( (1 974), and Cloutman ( 1975). Because length of host fish is a direct function of age in normal populations, results of studies by Colley and Olson (1963) and Avault and Allison (1965) also agree with observations on pond 1 bluegills.…”
Section: Discussionmentioning
confidence: 65%
“…Spall and Summerfelt (1970) found that female white crappies harbored P. minimum infections averaging twice the nurr~bers found in males and also reported that male bluegills, largemouth bass, and longear sunfish exhibited greater prevalence and intensities of P. minimum than females of these species. Host sex was not found to be associated with parasite abundance in an Arkansas impoundment (Cloutman 1975). P .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations